2023
DOI: 10.1101/2023.02.18.529076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is resting state fMRI better than individual characteristics at predicting cognition?

Abstract: Changes in spontaneous brain activity at rest provide rich information about behavior and cognition. The mathematical properties of resting-state functional magnetic resonance imaging (rsfMRI) are a depiction of brain function and are frequently used to predict cognitive phenotypes. Individual characteristics such as age, gender, and total intracranial volume (TIV) play an important role in predictive modeling of rsfMRI (for example, as "confounders" in many cases). It is unclear, however, to what extent rsfMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…Task fMRI (tfMRI) is of particular interest in the prediction of cognitive performance, given its success in mapping patterns of brain activity evoked by different tasks, identifying both distributed and specific neural responses to different processing demands. Our group and others have recently shown that task-evoked activation outperforms resting state functional connectivity measures when predicting cognition in the ABCD study [16][17][18] , and similar conclusions have been drawn in other samples of youth and adults [19][20][21][22] .…”
Section: Introductionsupporting
confidence: 81%
“…Task fMRI (tfMRI) is of particular interest in the prediction of cognitive performance, given its success in mapping patterns of brain activity evoked by different tasks, identifying both distributed and specific neural responses to different processing demands. Our group and others have recently shown that task-evoked activation outperforms resting state functional connectivity measures when predicting cognition in the ABCD study [16][17][18] , and similar conclusions have been drawn in other samples of youth and adults [19][20][21][22] .…”
Section: Introductionsupporting
confidence: 81%
“…A possible explanation for these findings is the lack of a common link between brain structure and sleep quality/depressive symptoms, as highlighted previously ( Olfati et al, 2024 ; Weihs et al, 2023 ; Winter et al, 2024 ). Similarly, literature assessing the combined effects of brain and behavioural information found no improvement, or even a decrease, in predictability when compared to using only phenotypic information ( Dadi et al, 2021 ; Krämer et al, 2023 ; Olfati et al, 2024 ; Omidvarnia et al, 2023 ). In our study, this is consistent with the results of the HCP Young sample, where the behavioural rCCA model showed the strongest associations to MP and the addition of GMV did not increase the canonical correlation.…”
Section: Discussionmentioning
confidence: 97%
“…This study aimed to assess the effects of foot re exology on an infant with SNHL using resting-state fMRI (rs-fMRI). rs-fMRI is safe and reliable for predicting cognitive phenotypes and measuring foot re exology responses ( [14],[6]). Compared with the control group, the treated infant exhibited increased ReHo values of the bilateral middle temporal cortex, the left frontal cortex, the right thalamus and the right caudate.…”
Section: Discussionmentioning
confidence: 99%